Peran Auditor Internal Dalam Pencegahan Kecurangan (Fraud) Pada Perguruan Tinggi Di Pekanbaru - Aprilia, Winda; Marlina, Evi; Agustiawan Agustiawan (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
This study aims to analyze the possible role of internal auditors in preventing fraud at universities in Pekanbaru. The object of this research are several universities in Pekanbaru. This type of research is qualitative research, the data collection of this research is done by interviews, observation, and documentation. The results of this study indicate that the role of the auditor is very important for fraud prevention and fraud control in university institutions, by going through several stages of internal audit procedurally. To prevent risks or losses, the internal auditors carry out the stages of tracing or identifying a fraud before the fraud actually occurs. So that these stages can be carried out effectively and efficiently. Keywords: The Role of Internal Auditors, Fraud, Universities.